USM SCHOOL OF MANAGEMENT 25th ANNIVERSARY: STRIVING FOR HOLISTIC GRADUATES WITH SOUL - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 19 August 2015 – The proud achievements of the School of Management (PPP), Universiti Sains Malaysia (USM) ever since its establishment in December 1989 until the present time, have encompassed various aspects in stamping its name as the pioneers of excellence among the providers of business management studies in the country, with acknowledgements from various international authorities in the efforts to produce excellent graduates who would be sought after by employers locally and abroad.